DESIGN AND MODELING OF HYBRID MICROGRIDS IN ARCTIC ENVIRONMENTS - Fish, Ruth (Monterey, CA; Naval Postgraduate School, 2020)
As the U.S. military shifts its efforts from the Middle East to the Pacific and the Arctic, energy planners must also refocus methods of designing and modeling energy management to support such missions. This thesis develops a methodology to size the energy resources of a military hybrid microgrid and implements this methodology in a user-friendly tool that is easily accessible to engineers and energy managers at military facilities. The tool focuses on increasing the resilience specifically of military microgrids and on accurately sizing distributed energy resources (DERs) to account for climate. While complying with IEEE standard 1562-2007, the tool allows the user to specify environmental factors of the location and decide upon the total dependence of the system on solar power. Three experiments with a commercial off-the-shelf (COTS) microgrid validated the design tool and physics-based model. Then, this research tested the performance of 30 differently sized DERs to understand the parameters for the design of hybrid microgrids for military installations in a range of climates. Finally, the research provides the tool user with guidelines for designing the DERs for energy redundancy or flexibility and economy. Approved for public release. distribution is unlimited Captain, United States Marine Corps http://archive.org/details/designandmodelin1094566072